Transformasi Digital dan Reproduksi Ketimpangan Sosial Ekonomi di Wilayah Perkotaan Indonesia - Muharrar, Ahmad Rizky; Lestari Wulandari, Diah (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2025)
Digital transformation in urban areas in Indonesia is progressing rapidly, but this process does not always result in socioeconomic equality. This article analyzes how digital transformation reproduces socioeconomic inequality in urban areas through differences in access, utilization, and economic outcomes from digital technology. This study uses an empirical literature analysis approach and a synthesis of quantitative findings from previous research examining the digital divide, income inequality, and the dynamics of urban development in Indonesia. The results show that urban areas with advanced digital infrastructure tend to strengthen the position of middle- and upper-income groups, while the urban poor face limitations in digital literacy, device access, and connectivity quality. This condition impacts digital job opportunities, access to technology-based public services, and economic participation. The findings also indicate that efficiency-oriented digital transformation policies have not been fully integrated with the social justice agenda. This article emphasizes the importance of an inclusive and spatially based digital policy approach to reduce the reproduction of socioeconomic inequality in urban areas in Indonesia.